Equitable and Inclusive Education through Continuous Professional Development of Teachers - Sharma, Adrishta; Angadi, G.R (Voices of Teachers and Teacher Educators, 2025)
This paper explores the impact of Continuous Professional Development (CPD) on the quality of in-service teacher education in India, with a particular focus on adopting equitable and inclusive educational practices. Through a critical analysis of 28 studies, the research synthesises five core themes that highlight the connection between CPD and the promotion of inclusive classrooms. These themes emphasise shaping inclusive educational policies, enhancing teacher preparedness through targeted training programmes, and leveraging technology to improve access and engagement for all students. The study stresses the need for dynamic CPD frameworks that adapt to the evolving educational landscape, fostering ongoing teacher development and ensuring alignment with national inclusivity goals. The findings suggest actionable strategies for policymakers and educators to create a fairer and inclusive educational system, ultimately augmenting learning outcomes for a diverse student population.